Interrogating the Future : Essays in Honour of David Fasenfest - Brass, Tom; Das, Raju (Social Sciences E-Books Online, Collection 2025., 2024)
Honouring David Fasenfest, who has not only conducted research spanning contexts from Detroit to Shanghai but is also a long-standing editor both of a social science journal and of its related book series, this festschrift addresses issues centr